Correlation Between Body Mass Index and Dysmenorrhea in Preclinical Female Students Aged 16-24 at The Hang Tuah University Medical Faculty, Surabaya - Widayanti, Linda Prasetyaning; Widawati, Puspita Retnaning (International Conference on Sustainable Health Promotion, 2018)
Primary dysmenorrhea is a menstrual pain in the abdominal area that occurs on the first day of menstruation, and generally, it becomes gynecological problems in women. It occurred because there is an enhancement of PGF2α which can cause excessive myometrium spasm and lead to abnormal uterine contraction, which the levels of prostaglandins in women with a BMI more than normal (overweight) higher than women with normal BMI. This study was observational analytic by using cross-sectional methods. The population of this study is female students at Medical Faculty of Hang Tuah University Surabaya was aged 16-23 year old. The study was conducted in February 2014 with a sample size of 50 people were taken by simple random sampling technique. The data were collected by measuring directly on the respondents to determine the BMI and the presence of primary dysmenorrhea. The results showed that primary dysmenorrhea was 56% in women with BMI more than normal (overweight). From the results obtained chi-square significance value of p=0,023 (p<0.05 ; α=0,05). It can be concluded that there was influence 1,8x between BMI and primary dysmenorrhea in female students aged 16-23 years in 2014 at the Medical faculty of Hang Tuah University Surabaya.